Prevalence of dental caries and associated risk factors among People Living with HIV/AIDS and HIV uninfected adults at an HIV clinic in Kigali, Rwanda. - Julienne Murererehe; Yolanda Malele-Kolisa; François Niragire; Veerasamy Yengopal (PLoS ONE, 2023)
Background Dental caries is among the most frequent oral conditions in People Living with HIV/AIDS (PLWHA). There is a lack of baseline information on dental caries prevalence and associated risk factors among PLWHA in comparison to HIV uninfected people in Rwanda. Objective This study was conducted to determine the prevalence of dental caries and associated risk factors among PLWHA and HIV uninfected adults at an HIV clinic of Kigali Teaching Hospital (CHUK) in Kigali, Rwanda. Methods A comparative cross-sectional study was conducted among 200 PLWHA and 200 HIV uninfected adults aged 18 years and above attending an HIV clinic of CHUK. An oral examination was performed by a calibrated examiner. Dental caries were assessed using the WHO Decayed (D), Missing (M), and Filled Teeth (F) index (DMFT). Descriptive statistics, Chi-square, t-tests, and multiple binary logistic regression were used to analyze data. Results Overall, a higher prevalence (50.5%) of PLWHA had experienced dental caries (DMFT>0) compared to HIV uninfected counterparts (40.5%) (p = 0.045). The prevalence of Decayed teeth (D) was also higher (23.5%) among PLWHA compared to HIV uninfected persons (13.6%) (p = 0.011). The Mean(SD) DMFT scores among PLWHA and HIV uninfected participants were 2.28 (3.68) and 1.29 (2.21) respectively (p = 0.001). After performing multiple binary logistic regression analysis, the predictors of dental caries in PLWHA were being female (OR = 2.33; 95%CI = 1.14-4.75), frequent dental visits (OR = 4.50; 95% CI = 1.46-13.86) and detectable RNA viral load (OR = 4.50; 95% CI = 1.46-13.86). In HIV uninfected participants, the middle age range (36-45 years), and frequent dental visits were significantly associated with dental caries (OR = 6.61; 95%CI = 2.14-20.37) and (OR = 3.42; 95%CI: 1.337-8.760) respectively. Conclusion The prevalence of dental caries was higher in PLWHA than in HIV uninfected counterparts. The reported higher prevalence of caries in PLWHA was associated with being female, detectable viral load, and frequent dental visits. Therefore, there is a need for effective oral health interventions specific to PLWHA in Rwanda to raise awareness of the risk of dental caries and provide preventive oral health services among this population. To ensure timely oral health care amongPLWHA, there is a need for an effort from policymakers and other stakeholders to integrate oral health care services within the HIV treatment program in Rwanda.